Penggunaan Peraturan Bupati Untuk Mengatur Harga Tanah Dalam Pengenaan Bea Perolehan Hak Atas Tanah Dan Bangunan - Budi Ispriyarso (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2018)
Abstract This study aims to describe the use of regent regulations to regulate land prices in the Imposition of Fees for Acquisition of Land and Building Rights. This research is a normative legal research that uses the regulatory approach. the results showed that the use of District Regulation as a basis for setting land prices in the imposition of BPHTB in Kendal district, was a regulation made for the purpose of legal certainty about land prices, but from the juridical aspects, the regent regulation was not based on the delegation of authority in Kendal district regulation. Regulating BPHTB. Then the estimated price of land as regulated in Kendal Regulation No. 10 of 2017 is based on location criteria, namely Settlements, Agricultural Land, and Housing). And the estimated price of land which is regulated in Kendal Regulation Number 10 of 2017, functions as a comparison. Keywords: Land Prices. BPHTB, Land Tax. Abstrak Penelitian ini bertujuan untuk menguraikan Penggunaan Peraturan Bupati Untuk Mengatur Harga Tanah Dalam Pengenaan Bea Perolehan Hak Atas Tanah Dan Bangunan. Penelitian ini merupakan penelitian hukum normatif yang menggunakan pendekatan peraturan perundang undangan. hasil penelitian menunjukan bahwa Penggunaan Perbup sebagai dasar untuk menetapkan harga tanah dalam pengenaan BPHTB di kabupaten kendal, merupakan peraturan yang dibuat tujuan kepastian hukum tentang harga tanah, namun dari aspek yuridis peraturan bupati tersebut tidak didasarkan pada adanya delegasi kewenangan yang terdapat dalam Perda kabupaten Kendal yang mengatur BPHTB. Kemudian Perkiraan harga tanah yang diatur dalam Perbup Kendal Nomor 10 Tahun 2017 didasarkan pada kriteria lokasi yaitu Pemukiman, Tanah Pertanian dan Perumahan). Dan Perkiraan harga tanah yang diatur Dalam Perbup Kendal Nomor 10 Tahun 2017,berfungsi sebagai pembanding. Kata Kunci: Harga Tanah. BPHTB, Pajak Tanah.